Computational Insights into the Inhibition of Influenza Viruses by Rupestonic Acid Derivatives: Pharmacophore Modeling, 3D-QSAR, CoMFA and COMSIA Studies - Muthusamy, Karthikeyan; Kirubakaran, Palani; Krishnasamy, Gopinath; Thanashankar, Raja R. (Combinatorial Chemistry & High Throughput Screening, 2015)
The pharmacophore modeling and 3D-QSAR studies were performed on a series of amino alkyl rupestonates (Rupestonic Acid) derivatives reported for H1N1, H3N2 and Influenza B virus, NA inhibition. In order to improve the efficacy of amino alkyl rupestonates derivatives, a four point pharmacophore model with one acceptor and three hydrophobic regions was developed. Furthermore, the 3D-QSAR model was generated based on the pharmacophore hypothesis (AHHH) for each subtype. The hypothesis was more significant with R2=0.9204, Q2=0.917 for H1N1, R2=0.8911, Q2=0.8905 for H3N2 and R2=0.8385, Q2=0.7043 for Influenza B virus. The 3D-QSAR results provided an invaluable insight into structure activity correlation and it was shown that the hydrophobic regions were crucial for inhibitory activity. CoMFA and COMSIA validation had been done by leave one out and no validation methods.
Keywords: 3D-QSAR